CLEAR: A Novel Approach to Ultrasound Equipment Homeostasis. (19th August 2018) - Prats, Michael I.; Nelson, Bret P.; Gold, Delia L.; Branditz, Lauren D.; Boulger, Creagh T.; Bahner, David P.
Abstract : Protocols for the sanitation and maintenance of point‐of‐care ultrasound (US) equipment are lacking. This study introduces the CLEAR protocol (clean, locate, energize, augment supplies, and remove patient identifiers) as a tool to improve the readiness of US equipment, termed US equipment homeostasis. The state of US equipment homeostasis in the emergency department of a single academic center was investigated before and after implementing this protocol, with an improvement in outcomes. These findings demonstrate that the CLEAR protocol can improve US homeostasis. CLEAR can function as a teaching tool to promote homeostasis as well as a checklist to assess compliance.